1990
DOI: 10.1042/bj2720239
|View full text |Cite
|
Sign up to set email alerts
|

Cell swelling inhibits proteolysis in perfused rat liver

Abstract: Exposure of isolated single-pass-perfused rat liver to hypo-osmotic media resulted in liver cell swelling and an inhibition of release of branched-chain amino acids. Similarly, cell swelling inhibited [3H]leucine release from perfused livers from rats in which liver proteins were prelabelled in vivo by intraperitoneal injection of L-[4,5-3H]leucine 16-20 h before the experiment. The effects of cell swelling on [3H]leucine release were fully reversible. [3H]Leucine release was also inhibited when cell swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 17 publications
1
75
1
Order By: Relevance
“…Although amino acids are known to be inhibitors of hepatic autophagic proteolysis, very little information is available regarding the mechanism by which they exert this effect [32, 331. In their stimulating studies on the control of proteolysis in the isolated perfused liver, Haussinger and coworkers [7,[9][10][11] recently proposed that the increase in cell volume following amino-acid influx is in part responsible for the inhibition of proteolysis by amino acids. They not only demonstrated that perfusion with hypo-osmotic media was able to mimic the anti-proteolytic effect of amino acids, but also that the inhibitory effect of several amino acids (but not all of them) could be directly attributed to their ability to induce cell swelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although amino acids are known to be inhibitors of hepatic autophagic proteolysis, very little information is available regarding the mechanism by which they exert this effect [32, 331. In their stimulating studies on the control of proteolysis in the isolated perfused liver, Haussinger and coworkers [7,[9][10][11] recently proposed that the increase in cell volume following amino-acid influx is in part responsible for the inhibition of proteolysis by amino acids. They not only demonstrated that perfusion with hypo-osmotic media was able to mimic the anti-proteolytic effect of amino acids, but also that the inhibitory effect of several amino acids (but not all of them) could be directly attributed to their ability to induce cell swelling.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments of Haussinger et al [ 9 ] , cycloheximide was not used and rates of proteolysis were measured either as the production of leucine from non-labelled livers or as ['Hlleucine from previously labelled liver protein in the presence of non-labelled (0.1 mM) leucine in order to prevent reincorporation of the label into protein. In our experiments, we used cycloheximide to inhibit simultaneous protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The portal pressure was routinely monitored with a pressure transducer (Hugo Sachs Electronics, Hugstetten, Germany) (20). The effluent K ϩ concentration was continuously monitored with a K ϩ -sensitive electrode (Radiometer, Munich, Germany); insulin-induced K ϩ fluxes were determined by planimetry of areas under curves (21). If not stated otherwise, the compounds used in this study did not affect portal perfusion pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the Src inhibitor PP-2 but not its inactive analogue PP-3 prevented proteolysis inhibition by insulin (Fig. 3B, Table II 3 H label release into effluent was monitored as a measure of hepatic proteolysis in liver perfusion experiments (21). Because of differences in the labeling of the animals in vivo, the release of radioactivity was set to 100% during control conditions in the identical perfusion experiment.…”
Section: Conditionmentioning
confidence: 99%
See 1 more Smart Citation